GROWTH AND YIELD OF THE GOLDEX MELON CROP INFLUENCED BY COVERAGE OF THE SOIL - MORAIS, Elís Regina Costa de; MAIA, Celsemy Eleuterio; NEGREIROS, Maria Zuleide de; ARAÚJO JUNIOR, Bernardo Bezerra de; MEDEIROS, José Francismar de (Scientia Agraria, 2008)
The objective of this work was to evaluate the growth and physiological indexes of the melon crop in function of degree-day accumulated and to determine the relationship between the physiological index and yield of the crop in covered soil with plastic film in the colors black, silver, yellow, and brown and of the uncovered soil like witness. The experiment was conducted in the Fazenda Santa Júlia Agrocomercial Exportadora de Frutos Tropicais Ltda, Mossoró-RN (May-July of 2003) in Oxissol, using the Goldex melon in a randomized experimental block design with four replications. The results showed that the absolute growth rate, the relative growth rate for the number of leaves and the index of the leaf area were influenced by the covered of the soil and decreased with the development of the plant, and also that the biggest productivity of marketable fruits was registered on the coverages of the soil with plastic.